Infant Feeding Practices and Maternal Factors in Vietnam: A Prospective Cohort Study - Nguyen, Phung Thi Hoang (Curtin University, 2020)
This thesis was part of a multi-centre prospective-cohort study conducted at six hospitals in Vietnam. Participants (n=1709) were interviewed six times from week 24-28 of pregnancy to twelve months postpartum. This thesis aims to ascertain maternal factors (gestational diabetes, physical activity during pregnancy, and caesarean birth) influencing infant feeding practices and to assess the impacts of prelacteal feeding and early formula feeding on infant health and hospitalisation during the first year of life.